1997
DOI: 10.1084/jem.185.9.1585
|View full text |Cite
|
Sign up to set email alerts
|

Direct Ex Vivo Analysis of Activated, Fas-sensitive Autoreactive T Cells in Human Autoimmune Disease

Abstract: The frequency of clonally expanded and persistent T cells recognizing the immunodominant autoantigenic peptide of myelin basic protein (MBP)p85-99 was directly measured ex vivo in subjects with typical relapsing remitting multiple sclerosis (MS). T cells expressing mRNA transcripts encoding T cell receptor (TCR)-α and -β chains found in T cell clones previously isolated from these subjects recognizing the MBPp85-99 epitope were examined. In contrast to frequencies of 1 in 105–106 as measured by limiting diluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 32 publications
6
64
0
Order By: Relevance
“…1C). It has been shown that the frequency of antigen-specific Th cells in peripheral blood is low, even after immunization [19][20][21]. We therefore confirmed a KLH-specific increase in CD154…”
Section: Cd4supporting
confidence: 75%
See 1 more Smart Citation
“…1C). It has been shown that the frequency of antigen-specific Th cells in peripheral blood is low, even after immunization [19][20][21]. We therefore confirmed a KLH-specific increase in CD154…”
Section: Cd4supporting
confidence: 75%
“…The frequencies of human antigenspecific Th cells or even T-regulatory cells responding to a specific antigen are usually low, ranging from 1:1000 to 1:1 000 000 [19]. We used antigen-reactive CD154 expression which allows the detection of antigen-specific CD4…”
Section: Introductionmentioning
confidence: 99%
“…It is now evident that the interaction of Fas with FasL regulates a large number of pathophysiologic processes of apoptosis, including autoimmune diseases (11,12). Previous studies have also confirmed the observation that apoptotic cells in various cell types are implicated as the source of autoantigen when stimulated with different proapoptotic stimuli (13).…”
supporting
confidence: 49%
“…24 However, subjects with active autoimmune disease are more likely to have a higher frequency of activated T cells than healthy control subjects. [25][26][27] Therefore, we designed a FACS isolation strategy in which non-CD4 þ T cells were eliminated and only the top 1% of CD4 þ CD25 þ high T cells were collected as the regulatory T-cell subset. We have reported elevated apoptosis levels and decreased function of the CD4 þ CD25 þ high T-cell subset isolated from subjects with recent-onset T1D and from multiple autoantibody-positive subjects.…”
Section: Discussionmentioning
confidence: 99%